Collaborative Written Feedback Experience: A Case Study of Indonesian EFL Students in an Essay Writing Class - Yanti Sri Rezeki (International Journal of Educational Best Practices, 2017)
Implementing collaborative written feedback instruction is a way to develop students’ awarenes of writing as a process, the benefits of peer review and feedback, and the important roles of peer interaction for learning. The current research aimed at understanding students’ experiences of providing and responding to written feedback in group. It specifically sought to answer these questions: 1.) What are students’ perceptions toward collaborative written feedback experience? 2) What are students’ collaborative written feedback practices? and 3). What factors affect students’ collaborative written feedback experience? Conducted as a qualitative case study, the research reported the collaborative written feedback experiences of a group of three undergradutae EFL students in Essay Writing course. Data were drawn from  observations, focus group interview, student reflective essay, and collection of related documents and artifacts. The findings show that students have positive perceptions toward collaborative written feedback instruction citing that it helps them improve their writing and develop their interpersonal skills. The study also reveals that changing roles in the group and the use of media paltform to communicate are among the strategies employed in collaborative written feedback practices. Factors such as peer’s characteristics, level of confidence and task seemed to have affected these practices. Suggestions on the ways in which collaborative written feedback instruction can be implemented effectively are also provided.